(untitled) - Coe, Stella (London, 1964)
Ikebana, the Japanese art of flower arrangement, has an appeal that has carried it far from its native land. All over the world, wherever flowers are loved and admired, interest in this ancuent art of Japan is ever on the increase. For from it have sprung modern styles that not only excite Western viewers but also enhance contemporary Western homes.
Keywords: Flower arrangement, japanese